2021
DOI: 10.3389/fmars.2021.647344
|View full text |Cite
|
Sign up to set email alerts
|

Cephalotoxins: A Hotspot for Marine Bioprospecting?

Abstract: Molluscs provided one of the pioneering approved pharmaceuticals from the seas: the painkiller ziconotide, developed from an ω-conotoxin isolated from cone snails. As marine biotechnologists are turning towards the immense range of novel bioproducts from marine invertebrates, little attention has been given to cephalotoxins, a group of obscure proteinaceous toxins produced by the salivary glands of coleoids, i.e., octopuses, squids and cuttlefishes. These toxins, for which there is empirical evidence for actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Furthermore, an organisms' proteome can help in species' identification (Mazzeo and Siciliano, 2016). A proteomic approach has been used in cephalopods to understand their colours, toxins, host-parasite relationships and their immune system (Gestal and Castellanos-Martínez, 2015;Roumbedakis et al, 2018;Albertin and Simakov, 2020;Gonçalves and Costa, 2021). These studies used tissues such as skin (Crookes et al, 2004), slime (Caruana et al, 2016), saliva (Cornet et al, 2014), and in cuttlefish cuttlebones (Pabic et al, 2017).…”
Section: Proteomicsmentioning
confidence: 99%
“…Furthermore, an organisms' proteome can help in species' identification (Mazzeo and Siciliano, 2016). A proteomic approach has been used in cephalopods to understand their colours, toxins, host-parasite relationships and their immune system (Gestal and Castellanos-Martínez, 2015;Roumbedakis et al, 2018;Albertin and Simakov, 2020;Gonçalves and Costa, 2021). These studies used tissues such as skin (Crookes et al, 2004), slime (Caruana et al, 2016), saliva (Cornet et al, 2014), and in cuttlefish cuttlebones (Pabic et al, 2017).…”
Section: Proteomicsmentioning
confidence: 99%
“…The anterior salivary gland of Octopus vulgaris increases the predation efficiency of the animal through its protein secretions (Ponte & Modica, 2017). The anterior salivary gland secretes the protein only and the secretion causes the paralyzing of prey (Gonçalves & Costa, 2021). The anterior and posterior salivary glands of O. vulgaris consist of tubules with three types of secretory cells.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with (Fernández-Gago et al, 2018;Yamate et al, 2021). Some authors (Ramachandiran et al, 2020;Dill-Okubo et al, 2021Gonçalves & Costa, 2021 suggested the anterior salivary gland of Octopus vulgaris secretes the mucus, but this is not accurate evidence because the anterior salivary gland gives a negative reaction to PAS (Periodic acid Schiff) stain. There is relatively no evidence about the secretion of mucopolysaccharide extractable from the anterior gland tissue or its mucous secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The current view is that the saliva is a chemical cocktail including tachykinins (i.e. Eledoisin from Eledone, Erspamer and Anastasi, 1962), OctTK 1, phospholipase A2, other proteins, and enzymes (e.g., peptidase, hyaluronidase, chitinase) that also play key roles in toxicity of coleoid venom, supplemented by other small organic molecules, peptides, and non-enzymatic proteins (for review see: Ruder et al, 2013;Gonçalves and Costa, 2021).…”
Section: Toxin Secretion By the Salivary Glands: A Cornucopiamentioning
confidence: 99%
“…Characterization of the molecular structure and composition of cephalotoxins is still incomplete (maybe except for Sepia esculenta cephalotoxin, Ueda et al, 2008). Apart from the glycosylation of the protein, characterization allowed the identification of conserved domains: EGF-like, Sushi, TSP type-1 and LDL-receptor class A (review in Gonçalves and Costa, 2021). Of particular interest is the epidermal growth factor (EGF) domain known to paralyse crustaceans via Na v block; cephalotoxins, should be described as EGF neurotoxins.…”
Section: Toxin Secretion By the Salivary Glands: A Cornucopiamentioning
confidence: 99%